Sonogram Testicular Relationships with Semen Quality of Kintamani Dog - I Wayan Nico Fajar Gunawan; Luh Made Sudimartini; I Wayan Wirata (Journal of Veterinary and Animal Sciences, 2021)
Ultrasonography is a high-end tool whose initial use to diagnose pregnancy and now being used for fetal development monitoring, birth prediction, diagnosis, and management of reproductive diseases. The aim of this study was to evaluate the initial relationship between body weight, testicular sonogram on the quality of semen collected from the basal Kintamani dogs which is expected to be useful in reproductive management of Kintamani dogs. The study used 10 male Kintamani dogs with healthy reproductive status. The tool used is in the form of an ultrasound for livestock, namely the Veterinary Ultrasound Scanner with a 5 MHz probe transducer, the image mode in the form of B-mode which will be displayed on the LCD with a size of 10 inches. Ultrasound examination is carried out in series every once a week. The semen examination was carried out immediately after the testicular ultasonography examination was carried out. No association was found between echogenicity and heterogeneity of the prostate gland or other size of the prostate gland and semen quality. Testicular volume, prostart and age did not affect the quality of Kintamani dog spermatozoa, while the testicular sonogram had an effect on the quality of Kintamani dog spermatozoa.